2015
DOI: 10.4236/health.2015.79134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Carica papaya</i> Leaf Extract on Serum Lipids and Liver Metabolic Parameters of Rats Fed a High Cholesterol Diet

Abstract: Hyperlipidemia plays an important role in the development of atherosclerosis, the main cause of death in the world. In this study, the lipid-lowering effect of Carica papaya leaf in rats fed with a high cholesterol diet was evaluated. Daily doses of C. papaya extract 0, 31, 62 or 125 mg/kg body weight were orally administered in 300 µl polyethylene glycol to hypercholesterolemic rats; it was also administered 62 mg/kg body weight of the extract to rats with normal diet. After a 20-day treatment, the animals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…A previous study demonstrated that papaya fruit aqueous extracts lowered lipid peroxidation, increased glutathione levels, and increased the activity of catalase and superoxide dismutase, as well as improving the immune status, as reflected by an increase in IgG and IgM levels in acrylamide intoxicated rats ( 8 ). Furthermore, papaya leaf possesses hypoglycaemic and hypolipidemic effects on rats fed a high cholesterol diet ( 9 ). Ripe papaya possess carotenoids and vitamin C ( 7 ): β-carotene, a subtype of carotenoids, exhibits an anti-hyperlipidaemic effect on spontaneously hypertensive rats, and dietary β-carotene is associated with a decreased serum lipid profile in hypercholesterolemic rats fed a high cholesterol diet ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that papaya fruit aqueous extracts lowered lipid peroxidation, increased glutathione levels, and increased the activity of catalase and superoxide dismutase, as well as improving the immune status, as reflected by an increase in IgG and IgM levels in acrylamide intoxicated rats ( 8 ). Furthermore, papaya leaf possesses hypoglycaemic and hypolipidemic effects on rats fed a high cholesterol diet ( 9 ). Ripe papaya possess carotenoids and vitamin C ( 7 ): β-carotene, a subtype of carotenoids, exhibits an anti-hyperlipidaemic effect on spontaneously hypertensive rats, and dietary β-carotene is associated with a decreased serum lipid profile in hypercholesterolemic rats fed a high cholesterol diet ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main effects related to reductions in body weight concomitant with the accumulation of fat, reflected in the percentage of body fat and reductions in the circumference of adipocytes, is the reduction in total cholesterol, LDL-c, and TG levels [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tropical fruits have the capacity to modify important biochemical markers that can help manage metabolic illnesses including cholesterol and blood sugar [21]. Tropical fruits such as papaya, [22], [23] watermelon, [24] and bananas [25], [26] can lower cholesterol levels.…”
Section: Adults Who Received Telehealth Interventions (Thi) Had Lower...mentioning
confidence: 99%